Aplicación web para mejorar la gestión documental de la empresa Sociedad Latinoamericana S.R.L. – Trujillo - Castrejon Chunga, Cesar Augusto (2023)
The main objective of this research work was to improve the document management _x000D_ of the company Sociedad Latinoamericana S.R.L. of Trujillo through the implementation of _x000D_ a web application._x000D_ The research design was experimental of the pre-experimental type with the pre thesis and post-thesis method, a sample of 134 sales contract records was taken, 134 sales _x000D_ contract searches and 104 sales contract reports were generated, using observation as a _x000D_ technique and registration form as an instrument._x000D_ Finally, with the results obtained, it was possible to demonstrate the hypothesis that _x000D_ the web application improves the document management of the company Sociedad _x000D_ Latinoamericana S.R.L. by 79.52%. of Trujillo